Using Geographic Information Systems And Large Historical Data Bases To Protect Public Health And The Environment - Borgianini, Stephen A.; Gentzler, Robert E.; Nardi, Peter; Lewis, Ryan (European Scientific Journal, ESJ, 2016)
The Lowcountry of South Carolina, USA experienced rapid growth and development as tourism and recreation replaced rural agriculture and silviculture land uses in the 1960’s. At that time no water and wastewater infrastructure existed. Septic systems and shallow drinking water wells were installed to service private homes. The pace of development increased dramatically in the 1970’s with the conversion of Hilton Head Island (Island) into a world class beach, tennis and golf resort destination. This new highdensity development included water and wastewater infrastructure; however, a few older, more rural sections of the Island still retain septic systems. Hilton Head Public Service District (PSD), the local water/wastewater utility, is planning to provide service to these remaining properties over the next few years by extending both water and sewer to affected residents. This study utilized Geographic Information Systems (GIS) and large digitized databases such as soil survey and wetland inventory data to map the distribution of soils and wetlands on Hilton Head Island that were identified as unsuitable for effective operation of septic systems. A hazard ranking scheme was developed and a hazard assessment conducted to determine which properties on the Island faced the greatest risk of septic system failure. The PSD would use the results of this study to prioritize which properties would be targeted for sewer and water line extension and connection to the affected residents. This way potential health risks and impacts to surface water quality by failing septic systems could be avoided in a cost-effective and expeditious manner.